2021
DOI: 10.1063/5.0044151
|View full text |Cite|
|
Sign up to set email alerts
|

Quasi-objective coherent structure diagnostics from single trajectories

Abstract: We derive measures of local material stretching and rotation that are computable from individual trajectories without reliance on other trajectories or on an underlying velocity field. Both measures are quasi-objective: they approximate objective (i.e., observer-independent) coherence diagnostics in frames satisfying a certain condition. This condition requires the trajectory accelerations to dominate the angular acceleration induced by the spatial mean vorticity. We illustrate on examples how quasi-objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(51 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…Head & Bandyopadhyay 1981) also face objectivity as a minimal self-consistency requirement. Yet the Q-, λ 2 -, Δand λ ci -isosurfaces used for this purpose are not objective and hence their predictions for observed material tracer patterns, or momentum transport blocking, cannot be accurate (see Haller 2005Haller , 2021. While correlations may exist between measured scalar concentrations and the features of these non-objective diagnostics (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Head & Bandyopadhyay 1981) also face objectivity as a minimal self-consistency requirement. Yet the Q-, λ 2 -, Δand λ ci -isosurfaces used for this purpose are not objective and hence their predictions for observed material tracer patterns, or momentum transport blocking, cannot be accurate (see Haller 2005Haller , 2021. While correlations may exist between measured scalar concentrations and the features of these non-objective diagnostics (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Westerweel et al 2009;Eisma, Westerweel & van de Water 2021), there can be no causal relationship. Several formal modifications of these vortex diagnostics have been proposed to make them objective, but only the approach of Liu, Gao & Liu (2019a); Liu et al (2019b) would be generally applicable, as found by Haller (2021). Yet, for lack of a direct connection to material mixing and transport, even correct objectivizations of the currently used Q-, λ 2 -, Δand λ ci -procedures for vortex identification would depend on their users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, it is possible to reconstruct invariant sets of a fractal nature in the phase space related to chaotic advection (see, e.g., Péntek et al, 1995;Cartwright et al, 1999;Tél et al, 2000;Speetjens et al, 2021). Recent important applications are connected to the exploration of Lagrangian coherent structures (Haller, 2015;Hadjighasem et al, 2017;Haller et al, 2018;Beron-Vera et al, 2018;Callies, 2021;Haller et al, 2021), mostly in the context of ocean flows.…”
Section: Introductionmentioning
confidence: 99%
“…Péntek et al, 1995;Cartwright et al, 1999;Tél et al, 2000;Speetjens et al, 2021). Recent important applications are connected to the exploration of Lagrangian coherent structures (Haller, 2015;Hadjighasem et al, 2017;Haller et al, 2018;Beron-Vera et al, 2018;Callies, 2021;Haller et al, 2021), mostly in the context of ocean flows.…”
Section: Introductionmentioning
confidence: 99%